The effect of digital marketing on customer relationship management in the education sector: Peruvian case - Oré-Calixto, Sofía (2021)
The objective of the research was to determine the impact of Digital Marketing on customer relationship management (CRM) in an educational institution in central Peru. The study was carried out from the quantitative approach, with a non-experimental correlational transactional research design. A questionnaire was applied to 228 parents between the ages of 30 and 50 who belong to an educational institution in the city of Concepción in Peru. Using the structural equations model, it was found that Content Marketing has a significant influence on the operational management of customer relationships (p <0.05), as well as on the analytical management of customer relationships (p <0.05). Regarding the Marketing of social networks, it was identified that it has a significant influence on the operational management of customer relationships (p <0.05), as well as on the analytical management of customer relationships (p <0, 05), because the media used by educational institutions are attractive to parents. It is concluded that Digital Marketing has a great impact on customer relationship management (CRM) in the educational sector of a city in central Peru.